Breeding for abiotic stress resistance in yam (Dioscorea Spp.) using biotechnology approaches: present practices and prospects - Agre, A.P.; Mondo, J.; Edemodu, A.; Matsumoto, R.; Asiedu, R.; Akoroda, M.O.; Bhattacharjee, Ranjana; Gedil, Melaku A; Adebola, P.O.; Asfaw, A. (Springer, 2022)
Yam (Dioscorea spp.) is an important crop providing food, income and medicine in tropics and subtropics. Major yam species in West Africa such as D. alata and D. rotundata are subject to several biotic and abiotic stresses throughout the cropping cycle and post-harvest periods, resulting in substantial tuber yield and quality trait losses. Abiotic stresses (heat, drought, low soil fertility, salinity, waterlogging, etc.) are currently exacerbated by the climate change effects. Yet, limited efforts exist in screening and developing yam varieties for those abiotic stresses. This book chapter reviews efforts of yam breeding programs in addressing yield losses associated with abiotic stresses and discusses perspectives in use of biotechnological tools for accelerating the development of abiotic stress resistant yam varieties.